Antifungal and antioxidant properties of medicinal plants used against fungal infections - Tambudzani C. Machaba; Salome Mahlo; Jacobus Eloff (AOSIS, 2024)
Background: Antioxidants present in plant extracts prevent free radicals from causing chronic diseases in humans. Aim: The study investigated 12 medicinal plants (Kleinia longiflora DC., Berchemia discolor [Klotzsch] Hemsl., Persea americana Mill., Sansevieria hyacinthoides [L.] Druce, Dichrostachys cinerea [L.] Wright Arn, Withania somnifera Dunal [Ashgandh], Momordica balsamina L., Lonchocarpus capassa, Pappea capensis, 'Rhus lancea L. fil' with 'Searsia lancea (L.F.) F.A. Barkley' Peltophorum africanum, Maytenus heterophylla [Eckl. Zeyh.] Robson) for antioxidant activity using the qualitative and quantitative 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Setting: The plant species were selected from the ethnomedicinal plant database of over 300 medicinal plants used for therapeutic purposes in Limpopo province. Methods: The plant materials were extracted with solvents of various polarities such as acetone, dichloromethane (DCM), methanol, hexane, and water. The qualitative and quantitative DPPH methods were used to determine the antioxidant activities of plant extracts. Results: The yellow bands revealed the presence of antioxidant compounds against the purple background on the Thin Layer Chromatography (TLC) plates. Methanol, hexane, and water extracts of L. capassa were the most active radical scavengers in the DPPH assay among the six medicinal plants screened. Plant extracts of P. africanum showed strong antioxidant activity by inhibiting DPPH, compared with the standard ascorbic acid. Conclusion: The findings indicate that some extracts can be used as an easily accessible source of natural antioxidants. Contribution: The findings revealed that the plant species investigated displayed noteworthy antioxidant activity, which provides scientific evidence for their utilisation by traditional health practitioners to treat fungal infections.